PENGARUH WAKTU PEMBERIAN OXYTOCIN DENGAN LAMA PENGELUARAN PLASENTA PADA KALA III PERSALINAN - Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Postpartumhemorrhage is bleeding or blood loss of more than 500 cc happens after the baby is born.Based on research conducted by Mu'minatunnisa (2011) are 3429 mothers whoexperience postpartum hemorrhage 8.8%, which is the cause of 51% by retainedplacenta. Normally placental separation occurred at 15 minutes after the newborn.Improved access to delivery by health personnel in health facilities will ensure thesuccess of giving oxytocin within one minute after the baby is born. The exact time ofgiving Oxytocin will shorten the time of placenta delivery. The delivery of the placentaÂ that is rapid and complete will reduce the risk of postpartum hemorrhage. This researchincludes the study of correlation analytic research with cross sectional approach. Theresearch variables were independent variables consist of giving oxytocin time in seconds.The dependent variable was the time of delivery the placenta in minutes. The datacollected by observation. The study population was all women giving birth in the periodDecember in Banyumas. The sampling technique used techniques accidental until thequota is achieved. Criteria sample was normal vaginal birth mothers without giving auterine tonic in any form other than uterotonic given to the third stage of labor.Univariate analysis to determine the frequency distribution of each variable, while thebivariatnya analysis used simple linear regression test.Â  The result of research are thedistribution of data is normal. Variable the time giving of the oxytocin, the mean value is54.14 and the standard deviation is 13 036. Variabel the time delivery of the placenta, themean value is 7.54 and the standard deviation is 2.7. The result of the significant value of0.000 is smaller than 0.005, which means Ho rejected. There is the effect of the givingoxytocin time to the timing delivery of the placenta on the third stage of labor, theregression equation is Y = 1,015 + 0. 121 (X), which means that every additional 1second the time of giving oxytocin, it will increase the long expulsion of the placenta for0121 minutes.Keywords: oxytocin, the third stage of labor